A família conta : ilustrações a partir do fado - Gonçalves, Ana (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
This article aims to contribute to an exploration of the relations between familial memoires and life course, specially stressing their dialogical and dynamic features. The focal point of this approach is the recognition that, on the one hand, family stories are subject to change over time and are deeply rooted in personal biographies, and, on the other hand, the memory is a central element of the individual's life course, which itself involves the possibility to know, live, remember and share meaningful experiences. A family linked to fado serves as an empirical illustration.